A Randomized Controlled Trial Assessing the Effects of a Pharmacist-Led Educational Pharmaceutical Care Program on Clinical and Self-Management Outcomes in Type 2 Diabetes Mellitus Patients in Gujarat, India - Patel, Rishita. D; Patel, Harsha V. (Indian Journal of Pharmaceutical Education and Research, 2026)
Objectives: The objective of the pharmacist-led educational Pharmaceutical Care Intervention Program (PLEPCIP) was to evaluate its effect on glycemic control, as measured by HbA1c levels, in patients with type 2 diabetes. Secondary outcomes included changes in blood pressure, lipid profile, body weight, medication adherence (assessed using the MMAS-4 scale), and self-management behaviors such as physical activity and dietary practices. Materials and Methods: Study was a prospective and longitudinal randomized controlled trial conducted in patients with type 2 diabetes at the OPD of a private diabetic hospital. A total of 280 patients enrolled; of these, n=139 patients were randomized to the Control Group (CG) and n=141 to the Interventional Group (IG). The duration of the present study was 16 months with 4 follow-up discussion sessions. Study outcome was measured at multiple visits, including baseline week 0 and follow-up weeks 16, 32, 48, and 64. Results: Patients in the intervention group demonstrated a statistically significant reduction in glycated hemoglobin (HbA1C) levels compared to the control group (mean reduction: 1.1% vs. 0.03%; p<0.001). Additionally, the intervention group exhibited significant improvements in Body Mass Index (BMI; p=0.049), systolic blood pressure (SBP; p=0.015), and Diastolic Blood Pressure (DBP; p=0.030). Triglyceride concentrations also decreased significantly within the intervention cohort (p=0.003). Furthermore, participants in the intervention group reported enhanced self-management behaviors, characterized by increased engagement in physical activity and adherence to a balanced dietary regimen. Medication adherence, as assessed by the Morisky Medication Adherence Scale, showed significant improvement (p<0.001), indicating better compliance with prescribed therapeutic protocols. Conclusion: A greater reduction in the HbA1C with overall metabolic outcomes was significantly associated with the clinical pharmacist-led educational Pharmaceutical Care Intervention Program (PLEPCIP) in type 2 diabetes mellitus patients.
Keywords: Structured Pharmaceutical Care Program; Education Intervention; Type-2 Diabetes; Mellitus; longitudinal study